The Routledge introductory course in biblical Hebrew - Kahn, Lily (Routledge, 2014)
"This complete course provides an accessible yet thorough introduction to biblical Hebrew language and texts. It employs an innovative approach based around a series of lively and memorable stories that serve to introduce the essentials of biblical grammar and vocabulary in an entertaining way. Each story is followed by clear and detailed grammatical explanations including helpful examples. There is a wide range of varied and dynamic exercises designed to reinforce new grammar and develop learners' ability to use biblical Hebrew actively. Each unit concludes with a genuine biblical text. These texts serve both to familiarize students with the main biblical narrative cycles and to equip them with the ability to read authentic material confidently from the earliest stages of learning. The textbook also features a convenient grammar summary and two-way glossary. The printed volume is accompanied by an extensive companion website containing numerous extra exercises and biblical texts; flashcards; a vocabulary guide listing words by part of speech; a full answer key with translations of all stories and biblical texts; teachers' resources including a sample syllabus and coursework covering the entire contents of the course; and audio recordings of the stories and biblical texts."--